INNOVATIVE METHODS IN TEACHING ENGLISH. - Rahmatullayeva Feruza Xolmuratovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
After the independence of our country, the interest in teaching foreign languages ​​has increased and many opportunities have been created for young people. New methods and requirements for foreign language teaching in the country have been developed in accordance with the Recommendations of the European Framework for Assessment of Knowledge and Skills of Foreign Language Teachers (CEFR). According to him, textbooks have been created for students of secondary schools and vocational colleges. In accordance with these requirements, classrooms are equipped with stands and new information and communication technologies. This article highlights the importance given to foreign languages ​​in the Republic of Uzbekistan and the innovative technologies needed to study them.